Mindfulness and Its Influence on the Well-being and Academic Performance of University Students (Docentes 2.0 Journal, 2025)
Mindfulness has emerged as an effective strategy to enhance emotional well-being, as well as academic performance, among university students who often experience high levels of stress and anxiety. Several studies support its benefits, highlighting notable reductions in anxiety symptoms, improvements in concentration, and emotional self-regulation. Programs such as MBSR (Mindfulness-Based Stress Reduction) have demonstrated their effectiveness in various cultural contexts, fostering a more balanced and resilient learning experience. This study aims to analyze how the implementation of mindfulness, particularly the MBSR program, can help higher education students manage or improve the emotional and academic challenges they face. The study's methodology was based on the positivist paradigm, using a pre- and post-experimental design with a control group, employing statistical techniques such as ANOVA to quantify significant variations. The findings showed significant progress in both academic and emotional indicators, with effect sizes ranging from moderate to high (Cohen's d between 0.55 and 0.80). In addition to numerical data, student statements indicated better control of academic stress and personal motivation. However, limitations were acknowledged, such as the lack of longitudinal studies and cultural diversity, suggesting the need to standardize and individualize programs. The discussion highlights that, while the effect of mindfulness is consistent, its effectiveness may vary depending on the context, requiring personalized interventions. In conclusion, the need to incorporate mindfulness into higher education is emphasized as an essential tool for students' holistic growth, suggesting future research to explore its mechanisms of action, as well as its usefulness in virtual and multilingual formats.
Keywords: Mindfulness; well-being; performance; university students